2022
DOI: 10.1101/2022.06.28.22276654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistence of pneumococcal carriage among older adults in the community despite COVID-19 mitigation measures

Abstract: Background. Reported rates of invasive pneumococcal disease were markedly lower than normal during the 2020/2021 winter in the Northern Hemisphere, the first year after the start of the COVID-19 pandemic. However, little is known about rates of carriage of pneumococcus among adults during this period. Methods. Between October 2020-August 2021, couples living in the Greater New Haven Area were enrolled if both individuals were aged 60 years and above and did not have any individuals under the age of 60 years … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Updated World Health Organization recommendations made in 2013 by the Pneumococcal Carriage Working Group advised the inclusion of oropharyngeal swabs from adults when possible [30]. A number of studies have demonstrated that the sensitivity of carriage detection can be further improved when molecular methods are applied [15,[31][32][33][34] to alternative sample types such as saliva [21,23]. With increased use of molecular methods however, there have been increased reports of confounding by non-pneumococcal species of Streptococcus, leading to uncertainty regarding the accuracy of culture-independent approaches [13,24,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Updated World Health Organization recommendations made in 2013 by the Pneumococcal Carriage Working Group advised the inclusion of oropharyngeal swabs from adults when possible [30]. A number of studies have demonstrated that the sensitivity of carriage detection can be further improved when molecular methods are applied [15,[31][32][33][34] to alternative sample types such as saliva [21,23]. With increased use of molecular methods however, there have been increased reports of confounding by non-pneumococcal species of Streptococcus, leading to uncertainty regarding the accuracy of culture-independent approaches [13,24,35].…”
Section: Discussionmentioning
confidence: 99%
“…The lytA -positive/ piaB -negative strains were thawed on ice, cultured on blood agar plates using a 10 μl inoculating loop and incubated overnight at 37ºC with 5% CO 2 . Colonies were harvested using a 10 μl inoculating loop and DNA was extracted via the boilate method [21]. For each strain, the 408 bp variable region of the rpsB gene encoding the ribosomal protein S2 was amplified with conventional PCR using the primers previously described [24] with a modified protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture-enriched saliva samples were thawed on ice. DNA was extracted from 200 μL of each sample using the MagMAX Ultra viral/pathogen nucleic acid isolation kit (Thermo Fisher Scientific) on the KingFisher Apex instrument (Thermo Fisher Scientific), with modifications ( 22 ). Each DNA template was tested by qPCR for the pneumococcal genes piaB ( 23 , 24 ) and lytA ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…A real-time qPCR assay targeting the pneumococcal iron uptake ABC transporter lipoprotein piaB gene was used to detect the presence of pneumococcal DNA in both the DNA extracted from culture-enriched samples and saliva lysates, as previously described. 12,19,20 Both DNA extracts and saliva lysates (2.5 µL) were tested in 20 µL reaction volumes using Advanced Universal Probe Supermix (BioRad, USA) and a primer/probe mix at concentrations of 250 nM (1 μL per reaction) (Iowa Black quenchers, USA).…”
Section: Molecular Detection Of Pneumococcal Carriagementioning
confidence: 99%